Two new species of Antrodia (Polyporales, Basidiomycota) in western China - Zhou, Hong-Min; Liu, Shun; Deng, Xiao-Juan; Liu, Hong-Gao; Xing, Rui; Dai, Yu-Cheng; Wu, Ying-Da (Frontiers in Microbiology, 2023)
Two new species of Antrodia, A. aridula and A. variispora, are described from western China. Phylogeny based on a six-gene dataset (ITS + nLSU + nSSU + mtSSU + TEF1 + RPB2) demonstrates that samples of the two species form two independent lineages within the clade of Antrodia s.s. and are different in morphology from the existing species of Antrodia. Antrodia aridula is characterized by its annual and resupinate basidiocarps with angular to irregular pores of 2–3 mm each and oblong ellipsoid to cylindrical basidiospores measuring 9–12 × 4.2–5.3 μm, growing on gymnosperm wood in a dry environment. Antrodia variispora is characterized by its annual and resupinate basidiocarps with sinuous or dentate pores with a size of 1–1.5 mm each and oblong ellipsoid, fusiform, pyriform, or cylindrical basidiospores measuring 11.5–16 × 4.5–5.5 μm, growing on the wood of Picea. The differences between the new species and morphologically similar species are discussed in this article.